Utility Function (Tingkat Kepuasan) Konsumen dalam Islam (Studi Prilaku Konsumen dalam Analisis Etika, Tujuan, Batasan, Fungsi dan Peningkatan Kepuasan dalam Perspektif Ekonomi Mikro Islam) - Siswadi Siswadi (Program Studi Ekonomi Syariah dengan Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2022)
The term consumption is not just eating or drinking, but is any use or use of goods and services that can directly satisfy one's needs. The purpose of consumption in Islam is to achieve happiness and prosperity in the world and the hereafter (Falah), so the way of consuming it must of course be based on Islamic values ​​and sharia in which it is not only concerned with material (worldly) aspects but also pays attention to other aspects of consumption. aspects of ukhrawi (hereafter). The method used in this research is literacy studies or library research. Literacy studies are written summaries of articles from journals, books, and other documents that describe theories and information both past and present, organizing literature into topics and documents needed. The type of data used in the author's research in this study is data obtained from the study of literature. From the data that has been obtained then analyzed by descriptive analysis method. Conclusions from this work include ethics or norms that must be considered in carrying out consumption activities, the purpose of consumption for a Muslim is as a means of help to worship Allah, the Qur'an provides very clear and easy-to-understand instructions.